Temporal Variability of Planktonic Ciliates in a Coastal Oligotrophic Environment: Mixotrophy, Size Classes and Vertical Distribution - Romano, Filomena; Symiakaki, Katerina; Pitta, Paraskevi (Frontiers in Marine Science, 2021)
Temporal variability of planktonic ciliates was studied in an extreme oligotrophic environment with special focus on trophic-modes and size-classes. Abundance, biomass, size-classes, mixotrophy vs heterotrophy, and species composition of planktonic ciliates were investigated focusing on temporal (samples collected monthly during 2019) and bathymetric (7 depth-layers in the euphotic zone, surface to 120 m) distribution at a coastal station in the oligotrophic Eastern Mediterranean. Abundance was generally very low (20 to 1130 cells L-1), except for September, which presented the highest abundance and biomass. Aloricate species dominated the ciliate community in all months and depths (% contribution from 77% in September to 99% in April). In general, oligotrichs presented maximum abundance at 2-10 m (except for June, July and November: 100-120 m) whereas choreotrichs were more homogeneously distributed (and showed maxima at deep chlorophyll maximum (DCM)). Small heterotrophs dominated the ciliate community at all depths and months, on average by 76% (they were 3-times more abundant than mixotrophs in terms of abundance and 2.5 times in terms of biomass). They were equally distributed vertically and seasonally (and also in terms of size-classes). In contrast, mixotrophs were found mainly at the surface layer to 20 m throughout the year, except for June and July (max at 100, 50 m). On average, 63% of integrated aloricate abundance was species <30µm, of which 25% were mixotrophs. During the stratification period of May to November, the very small (<18µm) and small (18-30µm) mixotrophic species were distributed throughout the water column whereas the >50 µm mixotrophic species were found only above the DCM. In contrast, during the mixing period of December to May, mixotrophic ciliates were very few and were dominated by small and medium-sized species. It seems that mixotrophic and heterotrophic ciliates, on one hand, and the four size classes, on the other, are very distinct groups characterized by different distributions both vertically and seasonally. This may have important consequences for the structure and function of the microbial food web they are a part of and the carbon flow to the higher trophic levels of this oligotrophic environment in which ciliates are the main grazers.